2010
DOI: 10.1172/jci38388
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Fas in adipocytes relieves adipose tissue inflammation and hepatic manifestations of obesity in mice

Abstract: Adipose tissue inflammation is linked to the pathogenesis of insulin resistance. In addition to exerting deathpromoting effects, the death receptor Fas (also known as CD95) can activate inflammatory pathways in several cell lines and tissues, although little is known about the metabolic consequence of Fas activation in adipose tissue. We therefore sought to investigate the contribution of Fas in adipocytes to obesity-associated metabolic dysregulation. Fas expression was markedly increased in the adipocytes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
161
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 151 publications
(180 citation statements)
references
References 55 publications
13
161
0
1
Order By: Relevance
“…Likewise, we previously reported that activation of the Fas signalling pathway in 3T3-L1 adipocytes increased the production of pro-inflammatory cytokines such as IL-6 and KC, without affecting cell viability [5]. Moreover, FasL-treated 3T3-L1 adipocytes became insulin resistant, as revealed by decreased insulin-stimulated glucose uptake and increased basal lipolysis [5]. However, the molecular mechanism involved in FasL-induced reduction in insulin-stimulated glucose uptake in 3T3-L1 adipocytes is not clear, and the present study seeks to unravel this mechanism.…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…Likewise, we previously reported that activation of the Fas signalling pathway in 3T3-L1 adipocytes increased the production of pro-inflammatory cytokines such as IL-6 and KC, without affecting cell viability [5]. Moreover, FasL-treated 3T3-L1 adipocytes became insulin resistant, as revealed by decreased insulin-stimulated glucose uptake and increased basal lipolysis [5]. However, the molecular mechanism involved in FasL-induced reduction in insulin-stimulated glucose uptake in 3T3-L1 adipocytes is not clear, and the present study seeks to unravel this mechanism.…”
Section: Introductionmentioning
confidence: 62%
“…1). However since Fas is still expressed in the stromal vascular fraction of adipose tissue, Fas is still present in adipose tissue of AFasKO mice [5], while it is almost completely absent in isolated adipocytes (Fig. 1A).…”
Section: Membrane-bound Fasl Signals Via Fas Receptormentioning
confidence: 98%
See 3 more Smart Citations